The Innovation of Islamic Education Learning Methods to Increase Student Engagement in Class VIII at SMP Muhammadiyah 07 Medan - Hafiza Husna (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This research aims to develop innovative learning methods that can increase student involvement in Islamic Religious Education classes. The approach used is qualitative descriptive with interview, observation, and documentation methods to identify students' challenges and needs in learning. Based on the results of the analysis, it was found that the use of interactive learning methods, such as group discussions, the use of educational technology, and contextual approaches that are relevant to students' daily lives, can significantly increase students' active participation. This innovation also encourages more collaborative and reflective learning, so that students can understand religious values more deeply and applicatively. Thus, innovative learning methods are expected to be able to create a more dynamic and participatory learning environment, as well as strengthen students' religious understanding.